The scientific validation of research in teaching of the Physical Education and Sport - Terrisse, André; Buznic-Bourgeacq, Pablo (Clinical Styles. The Journal on the vicissitudes of childhood, 2010)
Any scientific research poses the question of its validation, among others in the filed of human sciences where qualitative methods are favored, because of their object. How does the validation take place in the context of a teaching characterized by it's contingency, i.e.: by the impossibility to anticipate it's effects and by the "divided" structure of the instructor himself? on the basis of work achieved in the field of clinical didactic of the SPE (Sports and Physical Education), this article proposes to analyze the modalities of interpretation of the research results in order to specify the theoretical and methodological conditions of the construction of a case.